OCCURRENCE OF GLAUCOMA INCIDENCE AND DIABETES MELLITUS AT KMU MADURA EYE CLINIC - Riyadatus Solihah Solihah; M. Shofwan Haris; Rizal Umar (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Glaucoma is a disease of the eye characterized by increased intraocular pressure, atrophy of the optic nerve papillae, and reduced vision. Glaucoma can be caused by systemic disease or local disease of the eye. One of the systemic disorders that can trigger glaucoma is diabetes mellitus (DM). The purpose of this study was to determine the relationship between the incidence of glaucoma and a history of diabetes mellitus at the KMU Madura eye clinic. This research was conducted using analytic observational method with a case-control design using a retrospective approach. The sample in this study was obtained by quota sampling technique with a total of 557 patients. Patient data was taken within a period of 12 months from January 2022 – December 2022. Based on the results of observational analysis, it was found that 203 patients (36.44%) had glaucoma with a history of diabetes mellitus, while 354 patients (63.56%) had glaucoma without a history of diabetes mellitus. The results of the Chi-Square test between the prevalence of Glaucoma and a history of Diabetes Mellitus showed a p value = 0.000 (p≤0.05) and the results of the Fisher test between each type of Glaucoma and a history of Diabetes Mellitus only Primary Open Angle Glaucoma only showed there was relationship with the value of p value = 0.004 (p <0.05). The results of this study can be concluded that there is a significant relationship between the prevalence of glaucoma and a history of diabetes mellitus.